Transistores orgânicos ultracompactos produzidos por autoenrolamento de nanomembranas - Torikai, Kleyton [UNESP] (2018)
In the recent years, the organic electronics’ commercial viability and competitiveness became apparent, integrating a diversity of technologies, e.g., OLED flexible displays, large-area solar panels and biocompatible and wearable devices. The manufacturing of electronic devices with organic materials aims at exploiting inherent characteristics— mechanical flexibility, low processing temperatures and the potential of boosting and tailoring specific properties through chemical synthesis. However, there’s still a gap between the well-established inorganic and the organic electronics concerning applications on rugged electronics, since the organic semiconductors (OSCs) are very susceptible to harsh conditions, e.g., exposition to UV radiation and gases. In this sense, recent advances on strained nanomembrane (NM) technology has shown enormous potential in the manufacturing of hybrid ultracompact devices in a novel organic thin-film transistor (OTFT) architecture. Through traditional microfabrication techniques—photolithography, thin-film deposition—OTFTs were fabricated on top of strained NMs, which promotes a reshaping of the devices into a 3D tubular architecture when released from the substrate. This process promotes a reduction in about 90% of the footprint area while protecting the OSC in the active area in between the multiple device windings. Therefore, the OTFTs have been endowed with new proprieties without loss of electric performance, while enduring hundreds of mechanical compression cycles and showing increased resilience against UV radiation and hazardous vapors, such as ammonia. Finally, to validate this novel OTFT architecture, this strategy has been shown to be valid for different OSCs and can be used to manufacture electronic circuits through the association of multiple devices, such as the inverter reported in this study.